2017
DOI: 10.1007/s11356-017-0285-7
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated diphenyl ethers (PBDEs) in background air around the Aegean: implications for phase partitioning and size distribution

Abstract: The occurrence and atmospheric behavior of tri- to deca-polybrominated diphenyl ethers (PBDEs) were investigated during a 2-week campaign concurrently conducted in July 2012 at four background sites around the Aegean Sea. The study focused on the gas/particle (G/P) partitioning at three sites (Ag. Paraskevi/central Greece/suburban, Finokalia/southern Greece/remote coastal, and Urla/Turkey/rural coastal) and on the size distribution at two sites (Neochorouda/northern Greece/rural inland and Finokalia/southern G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…Here, we would argue that over the next decades, an increase or a steady state in the atmospheric concentrations of low brominated PBDEs may occur and that the congener profile will likely be dominated by those lighter congeners which are more prone to revolatilization (and have a higher persistency) and hence have a higher potential for long-range atmospheric transport. The fact that, in this study, no significant decrease was observed for BDE47 in comparison to BDE99, even though it originates from the same penta mixture and is known to be a debromination product of BDE99 (Bezares-Cruz et al, 2004), supports this hypothesis. However, monitoring air concentrations over a longer time span is needed to provide further evidence.…”
Section: Inter-annual and Seasonal Variationssupporting
confidence: 75%
See 1 more Smart Citation
“…Here, we would argue that over the next decades, an increase or a steady state in the atmospheric concentrations of low brominated PBDEs may occur and that the congener profile will likely be dominated by those lighter congeners which are more prone to revolatilization (and have a higher persistency) and hence have a higher potential for long-range atmospheric transport. The fact that, in this study, no significant decrease was observed for BDE47 in comparison to BDE99, even though it originates from the same penta mixture and is known to be a debromination product of BDE99 (Bezares-Cruz et al, 2004), supports this hypothesis. However, monitoring air concentrations over a longer time span is needed to provide further evidence.…”
Section: Inter-annual and Seasonal Variationssupporting
confidence: 75%
“…This lack of temperature dependence has been previously attributed to long-range atmospheric transport (Hoff et al, 1998;Wania et al, 1998b). However, at least for BDE28, we suggest that the photolytic debromination of higher brominated congeners (Bezares-Cruz et al, 2004;Wei et al, 2013) may also play a role. In the case of the remaining congeners, the strong influence of ambient temperature on the gaseous concentrations of PBDEs, characterized by the high slopes in Table S10, has often been interpreted by previous studies (Cetin and Odabasi, 2008;Davie-Martin et al, 2016) as a demonstration that PBDE gaseous concentrations are controlled by revolatilization from surfaces (soil or water).…”
Section: Factors Affecting the Inter-sample Variationssupporting
confidence: 57%
“…In nature, atmospheric particles exhibit a wide range of sizes, where the concentrations of SVOCs vary, with fine particles (< 0.49 μm or around 1 μm (Besis et al, 2015(Besis et al, , 2017Luo et al, 2014;Lyu et al, 2016;Mandalakis et al, 2009;Su et al, 2018)) accounting for most of the concentration. Several research groups have studied the distributions of SVOCs in the size-segregated particles, most of them targeting polycyclic aromatic hydrocarbons (PAHs) (Chrysikou et al, 2009;Degrendele et al, 2014;Gutierrez-Daban et al, 2005;Kaupp and McLachlan, 1999;Oliveira et al, 2011;Venkataraman et al, 1999;Yu and Yu, 2012), PCDD/Fs (Degrendele et al, 2014;Kaupp and McLachlan, 1999;Lee et al, 2008), PBDEs (Besis et al, 2015(Besis et al, , 2017Luo et al, 2014;Lyu et al, 2016;Mandalakis et al, 2009;Okonski et al, 2014;Su et al, 2018;Zhang et al, 2012), polychlorinated biphenyls (PCBs) (Chrysikou et al, 2009;Degrendele et al, 2014), and OCPs (Chrysikou et al, 2009). Therefore, the G/P partitioning behavior of SVOCs varies among particle sizes, which implies that size-resolved G/P partitioning behavior of SVOCs would be different than partitioning behavior for bulk particles (de la Torre et al, 2018;Jin et al, 2017b;Offenberg and Baker, 2002;Venkataraman et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric levels of PBDEs depend on deposition processes, weather conditions, long-range atmospheric transport, and the proximity of PBDE sources to the sampling site (urban/industrial or background locations). A recent study monitored atmospheric PBDE levels (PBDE 28,47,85,99,100,153,154,183,and 209) in Central Europe, and the results indicate a global increase in low-bromine PBDEs in atmosphere [42]. This effect is due to the photolysis process, which favors the de-bromination of PBDEs with a higher bromine content.…”
Section: Environmental Pollution and Health Of Respiratory Systemmentioning
confidence: 99%